A survey of purchasers of wheat middlings: storage, feeding practices, and problems - Warmann, G.W.; Behnke, Keith C.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We surveyed 290 purchasers of wheat middlings (WM) from a single flour mill located in central Kansas to characterize the incidence of transport and storage problems and to determine intended animal us e and method of feeding. Over 30% of the 106 respondents had encountered storage problems with WM; mold, spoilage, and bridging in the storage structure were the most common. Over 75% of the respondents who reported no storage problems purchased WM during the winter months and avoided WM purchases at other times, especially during the summer.
Keywords: Beef; Wheat Middlings; Storage; Survey